PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOLABORATIF TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SENI RUPA MIS DARUSSA'ADAH PALANGKARAYA - Aprilia, Rida; Supriadi, Gito; Rizal, Setria Utama (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study aims to: (1) Describe the application of the Collaborative Learning Model in the subject of Fine Arts for grade IV at MIS Darussa'adah Palangka Raya, (2) To determine the learning motivation of students before and after the use of the Collaborative Learning Model on the learning motivation of students in the subject of Fine Arts for grade IV at MIS Darussa'adah Palangka Raya, (3) To determine the effect of the use of the Collaborative Learning Model on the learning motivation of students in the subject of Fine Arts for grade IV students at MIS Darussa'adah Palangka Raya. The sample of this study was all grade IV students at MIS Darussa'adah Palangka Raya, totaling 19 students. This study used observation and questionnaires as data collection instruments. (1) Based on data analysis, it was found that the application of the collaborative learning model obtained an average value of 95.73 which is categorized as Very Good, (2) Students' motivation to learn fine arts before treatment obtained 63.75 which is categorized as Sufficient, while students' motivation to learn fine arts after treatment was 82.04 which is categorized as Very Good, (3) The effect of using the collaborative learning model on students' motivation to learn in the Fine Arts subject for students in class IV at Mis Darussa'adah Palangka Raya obtained a significant value of less than 0.05, namely 0.000, so the hypothesis in this study is accepted.